Analysis of IT Governance COBIT 5.0 (Case Study: Ministry of Religious Affairs of Batam) - Suwarno Suwarno (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
Indonesian Government has developed technology-based information systems in their respective environments as an effort to realize public services that meet standards and achieve citizen service satisfaction, and in line with that as the government's efforts to digitize each business process in the government itself. Ministry of Religious Affairs of Batam that has developed this technology-based information system in implementing activities public services at Sekupang office, KUA, and integrated service places. This study aims to analyze the IT governance that has been applied at Ministry of Religious Affairs of Batam in providing public services. This study uses COBIT 5.0 to analyze IT governance in understanding and finding common ground between the needs of Batam citizen and the strategic plan of the Ministry of Religious Affairs of Batam, as well as how to evaluate and monitor IT governance in the actual conditions. This study uses two domains: Plan and Organize (PO) and Monitor and Evaluate (ME), based on the results of questionnaire data processing with 106 respondents, and the average value of the PO domain 3.8 and ME domain 3.9 shows that IT governance is at the Defined Process level. . Found two IT processes with a value of less than 3, namely PO8.1 and PO9.1, it is necessary to recommend improvements to quality management and risk management.